2015
DOI: 10.1002/cjce.22368
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of waste‐soap and soap‐like materials into diesel and gasoline by catalytic pyrolysis using virgin soap as model

Abstract: In this work, soap was converted into a hydrocarbon‐rich product through catalytic pyrolysis using cement as a catalyst. The intention was to develop a new economical and effective method for preparing diesel and gasoline from soap waste in food processing. The optimum conditions for pyrolysis were investigated in a batch process under static conditions at different reactor temperatures, catalyst amounts, and reaction durations. The resulting oil product was analyzed using GC‐FID, GC‐MS, and FTIR. The best yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The catalytic pyrolysis of fresh, putrefied, and microbe treated biomass was investigated in the range of 200–600 °C using a clinkered brick powder as catalyst. It has been reported that a change in temperature significantly effects the relative amount of each of the oil, gas, and char or residue fraction. , Earlier workers reported larger quantities of the char at temperatures lower than 400 °C; however, at higher temperatures, a large amount of the gas was produced. Similar results are reported in the presented work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The catalytic pyrolysis of fresh, putrefied, and microbe treated biomass was investigated in the range of 200–600 °C using a clinkered brick powder as catalyst. It has been reported that a change in temperature significantly effects the relative amount of each of the oil, gas, and char or residue fraction. , Earlier workers reported larger quantities of the char at temperatures lower than 400 °C; however, at higher temperatures, a large amount of the gas was produced. Similar results are reported in the presented work.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group considers the cost, availability, and effectiveness of both the biomass and catalyst. We have previously reported upgraded bio-oils produced by the catalytic pyrolysis of the water hyacinth using cement as a catalyst . Cement is a low cost clinkered material having solid oxides and reactive pores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation